Depression among Athlete Students and Differences by Gender at Physical Education of Bengkulu University in 2022 - Diah Ayu Aguspa Dita; Yahya Eko Nopiyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The Indonesia National Adolescent Mental Health Survey (I-NAMHS), over a third of all adolescents (34.9%) reported a mental health problem, with depression in third position in mental health problems (5.3%). High levels of physical activity and low sedentary behavior of athlete students have been associated with improved self-concept and reduced mental health problems, such as depression. As a result, depression has received little attention in this population. To describe the prevalence of symptoms of depression among athlete students at a single university. This cross-sectional study was administered to undergraduate students enrolled in physical education, faculty of teacher training, and education at the University of Bengkulu. Participants (n=70) completed the Beck Depression Inventory-II (BDI-II) and a demographic questionnaire. Differences in symptoms of depression were calculated by gender. The prevalence of symptoms of depression, as measured on BDI-II, was 36%, and there is no significant gender difference in the prevalence of symptoms of depression (p>0.05, distributed between male and female participants (52% women and 24.4% men). The BDI-II identified the prevalence of symptoms of depression among athlete students. The symptoms of depression in female students were higher than in male students.